PENGGUNAAN METODE BENEISH RATIO INDEX DALAM PENDETEKSIAN FRAUD DALAM LAPORAN KEUANGAN PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2019-2021 (Studi Kasus Pada Sektor Farmasi) - Dede Pramurza (Bajang Institute, 2023)
This research aims to: 1. What percentage of pharmaceutical companies on the IDX Preode in 2019-2021 are classified as manipulators? 2. What percentage of Pharmaceutical companies on the IDX Preode in 2019-2021 are classified as Non-Manipulators? 3. What percentage of pharmaceutical companies on the IDX Preode for 2019-2021 are classified as Gray Campanies? The research methodology used is descriptive qualitative and quantitative descriptive approaches. Research results namely; 1. The percentage of manipulator companies in pharmaceutical companies in 2019 is 12.5%, in 2020 it is 7.5% and in 2021 it is 7.5%. 2. The percentage of non-manipulator companies in pharmaceutical companies in 2019 is 67.5%, in 2020 it is 75% and in 2021 it is 77.5%. 3. The percentage of gray companies in pharmaceutical companies in 2019 is 20%, in 2020 it is 17.5% and in 2021 it is 15%